The role of NO in signaling pathway in cardiac ischemic preconditioning against myocardial ischemia-reperfusion injury - L. M. Danilenko (Ведомости Научного центра экспертизы средств медицинского применения, 2018)
Many recent studies have confirmed the effect of NO and that its relative signaling pathway is important for preconditioning of the cardioprotective effect. Mitochondria as a target for the cardioprotective effects of nitric oxide in ischemia-reperfusion injury is considered to be the ultimate goal of cardioprotection. During preconditioning, signaling is initiated from the sarcolemmal membrane and then spread into the cytoplasm via many series of enzymes, including nitric oxide synthase (NOS), soluble guanylyl cyclase (sGC), and protein kinase G (PKG). As a result, the signal is transmitted into the mitochondria, where the cardioprotective effect occurs. It is now well established that mitochondria act to protect the heart against ischemia-reperfusion injury via the opening of the mitochondrial ATP-sensitive K+ channel and the inhibition of mitochondrial permeability transition. This knowledge may be useful in developing novel strategies for clinical cardioprotection from ischemia-reperfusion injury.